PENYELESAIAN TINDAK PIDANA PENIPUAN DENGAN MENGGUNAKAN CEK KOSONG DI KEOPILISAN DAERAH RIAU - Sitinjak, Pramboy H; Hendra, Rahmad; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Rapid economic growth and complex spawned various forms of business cooperation, which is increasing day by day. The increasing business cooperation, causing the higher the level of disputes between the parties involved. In the current business cooperation the government's efforts to develop payment traffic that are demand deposits. One of payments that are demand deposits is a check. But in its use checks mischaracterized its use is by issuing a blank check. Dilhat from the perspective of criminal law the issuance of bad checks is included in the criminal fraud. police which is the most important element in the judicial system to perform legal settlement against crime.This type of research can be classified into types of juridical sociological research, because in this study the authors directly conduct research on a study in order to give a complete and clear picture of the problems examined. This research was conducted at the General Directorate of Criminal Investigation Police of Riau, while the overall population and the sample is related to the issues examined in this study, the data source used, primary data, secondary data and data tertiary data collection techniques in this study with interview and literature study.From the research there are three basic problems that can be inferred. First, the completion of the crime of fraudulent use of a blank check in the Directorate General of Criminal Investigation Police of Riau, has not run optimally. Second, obstacles in the completion of the crime of fraud using a blank check in the Directorate General of Criminal Investigation Riau Regional Police is investigating the lack of the number of members, geographical factors, factors the absence of witnesses. Third, efforts to overcome the obstacles in the completion of the crime of using a blank check at the General Directorate of Investigation Krimainal Riau Regional Police investigators are increasing the number of personnel, in collaboration with relevant institutions, the investigator requested the expert testimony. Suggestions writer, first, the government has set a ban on the withdrawal formerly blank check so that the law is reinstated, but the sanctions should be, Secondly, as the frontline in a legal settlement in Indonesia, the police must be more synergy and further improve coordination with the parties Another and improve quality in dealing with any offenses exist, Third, the public is advised to be more careful in the sale and purchase or other agreement to use checks as a means of payment.Keywords: settlement of criminal offenses - fraud - police